Lapaea (Plantaginaceae, Gratioleae), a new genus endemic to the Espinhaço Range (Brazil) with a remarkable red-flowered new species. Issue 8 (16th November 2020) - Scatigna, André Vito; Souza, Vinicius Castro; Machado, Raquel Moura; Simões, André Olmos
Abstract : Stemodia sensu lato is one of the largest genera of the Gratioleae (Plantaginaceae). Recent phylogenetic studies corroborated the paraphyly of Stemodia in its traditional circumscription and suggested the segregation of S. stellata from this genus. This species belongs to a morphologically cohesive group along with S. cipoensis, S. harleyi and S. lobata, all endemic to the Espinhaço Range, eastern Brazil. In this study, we tested the monophyly and interspecific relationships of this group by reconstructing its phylogeny, based on sequences of three cpDNA regions ( rps16 and trnL introns and the trnL – trnF intergenic spacer), and one nrDNA region (ITS1 spacer), using Maximum parsimony and Bayesian inference. The monophyly of the ' S. stellata group' was confirmed, and its segregation from Stemodia corroborated. We propose Lapaea as a new genus to accommodate its species, with subsequent four new combinations: L. cipoensis, L. harleyi, L. lobata, and L. stellata . Additionally, we describe and illustrate L. rubriflora, a remarkable red-flowered new species, based on morphological and micromorphological evidence. Lastly, a taxonomic revision of the species recognized in Lapaea is presented, providing an identification key, photos, descriptions, distribution map and notes on their morphology, geographic distribution, habitat, ecology, and conservation status. Lapaea is restricted to the Espinhaço Range comprising five threatened species, each of them with a narrow distribution and phylogenetic relationships consistent with biogeographic provinces.